EP322/#302 Information needs of lynch syndrome and BRCA 1/2 mutation carriers considering risk-reducing surgery: a qualitative study of the decision making process. (4th December 2022) - Zhao, Lucy; Eiriksson, Lua; Lynch, Lorrie
Abstract : Objectives: Risk-reducing surgery (RRS) may be offered to BRCA and Lynch syndrome mutation carriers to reduce risk of gynecological cancer. This study was conducted to better understand patients' information needs when navigating the decision-making process surrounding RRS and how patients weigh different sources of information in their decision-making process. Methods: This study used a qualitative approach to understand patients' perspectives towards RRS. Semi-structured interviews were conducted virtually. Inclusion criteria included women offered RRS between 35 and 70 years of age with an identifiable BRCA or LS mutation. Data from interviews was coded with constant comparative analysis to develop themes. Results: Of eight participants, six made decisions regarding RRS; five decided yes to RRS; one decided no. Two were undecided. Thematic analysis found that the key factors affecting patient's decisions around prophylactic surgery were cancer risk, surgical menopause, and psychological readiness. To make an informed decision, patients relied most heavily on information provided by healthcare professionals and family members with prior cancer experience. Information from friends and the Internet also contributed to decision-making. However, some participants reported feeling inadequately informed and identified COVID-19 as a significant barrier affecting access to information. Conclusions: This qualitative study revealed the key sources of information influencing attitudes regarding risk-reducing surgery. Results underscore the need for greater attention to patients' information needs in the context of psychological readiness, particularly amidst the pandemic. Research involving a larger sample size may help to better support the information needs of individuals with BRCA and LS mutations considering risk-reducing surgery.